Biogeographic congruency among bacterial communities from terrestrial sulfidic springs - Headd, Brendan; Engel, Annette S. (Frontiers in Microbiology, 2014)
Terrestrial sulfidic springs support diverse microbial communities by serving as stable conduits for geochemically diverse and nutrient-rich subsurface waters. Microorganisms that colonize terrestrial springs likely originate from groundwater, but may also be sourced from the surface. As such, the biogeographic distribution of microbial communities inhabiting sulfidic springs should be controlled by a combination of spring geochemistry and surface and subsurface transport mechanisms, and not necessarily geographic proximity to other springs. We examined the bacterial diversity of seven springs to test the hypothesis that occurrence of taxonomically similar microbes, important to the sulfur cycle, at each spring is controlled by geochemistry. Complementary Sanger sequencing and 454 pyrosequencing of 16S rRNA genes retrieved five proteobacterial classes, and Bacteroidetes, Chlorobi, Chloroflexi, and Firmicutes phyla from all springs, which suggested the potential for a core sulfidic spring microbiome. Among the putative sulfide-oxidizing groups (Epsilonproteobacteria and Gammaproteobacteria), up to 83% of the sequences from geochemically similar springs clustered together. Abundant populations of Hydrogenimonas-like or Sulfurovum-like spp. (Epsilonproteobacteria) occurred with abundant Thiothrix and Thiofaba spp. (Gammaproteobacteria), but Arcobacter-like and Sulfurimonas spp. (Epsilonproteobacteria) occurred with less abundant gammaproteobacterial populations. These distribution patterns confirmed that geochemistry rather than biogeography regulates bacterial dominance at each spring. Potential biogeographic controls were related to paleogeologic sedimentation patterns that could control long-term microbial transport mechanisms that link surface and subsurface environments. Knowing the composition of a core sulfidic spring microbial community could provide a way to monitor diversity changes if a system is threatened by anthropogenic processes or climate change.